Do Demographic Characteristics Make Differences? Demographic Characteristics as Moderators in the Associations between Only Child Status and Cognitive/Non-cognitive Outcomes in China - Liu, Ning; Chen, Yiting; Yang, Xiangdong; Hu, Yi (Frontiers in Psychology, 2017)
Different family compositions and sizes may affect child development through the different modes of interaction between family members. Previous studies have compared only children with non-only children in cognitive/non-cognitive outcomes. However, relatively little research has systematically investigated the potential moderators among them. Using a large and representative sample of Chinese students (Grades 7–8; N=5752), this study examines the roles of demographic characteristics, such as gender, region, parental educational level, parental expectations, family socio-economic status and family structure, in the associations between only child status and cognitive/non-cognitive outcomes. For the cognitive outcomes, only child status exerts an influence on the students’ academic performance in Chinese and mathematics in the sample of three districts’ students. The examined associations between only child status and cognitive outcomes are different in region, parental education, parental expectations and family structure, while gender and socio-economic status did not. For the non-cognitive outcomes, only child status exerts an influence on the students’ school well-being, academic self-efficacy, academic self-concept and internal academic motivation in the full sample of students, but not on external academic motivation. Further, The examined associations between only child status and non-cognitive outcomes are different in region, parental education, socio-economic status and family structure, while gender and parental expectations did not. These findings suggest that the associations between only child status and cognitive/non-cognitive outcomes are heterogeneous in terms of some of the demographic characteristics. Possible explanations are proposed in some concepts of region and family environment in China.